The Effectiveness of the Timeline Method on Student Learning Outcomes in Islamic Cultural History Class 4 MI PAS Baitu-l-Quran Gontor - Madani Ahmadan; Candra Wisnu Pratama (Universitas Negeri Semarang, 2026)
This study explores the efficacy of the Timeline method on the academic performance of fourth-grade students in Islamic Cultural History at MI PAS Baitul Quran Gontor. The Timeline method presents events chronologically to help students better understand historical sequences. A quantitative experimental approach with a Pretest-Posttest Control Group Design was used. Forty students were selected through Simple Random Sampling, with 20 in both experimental and control groups. Data was analyzed using the Mann-Whitney U test with SPSS software. The results indicate a significant difference between the experimental class, which used the Timeline method, and the control class. The experimental class's post-test average was 85.25 compared to the control class’s 71, supported by a Mann-Whitney significance value of Sig. (2-tailed) 0.000 < 0.05. This shows the Timeline method's effectiveness in improving learning outcomes in Islamic Cultural History. Recommendations include encouraging students to enhance motivation and understanding, supporting educators in using innovative teaching methods, and urging institutions to foster creativity in the learning process.